A state roadway incident e-detection and e-characterisation system. (5th October 2011) - Moynihan, Gary P.; Brumback, Terry; Fonseca, Daniel
The purpose of this research was to develop a computer-based road incident detection and characterisation system. It was designed for incorporation and enhancement of an existing traffic monitoring system used by the South Carolina Department of Transportation (SCDOT) Based on the requirements, a fuzzy logic approach was selected and adapted as the algorithmic processor for the decision support system. A working prototype system was then constructed in the first phase of development. This paper focuses on the second phase, primarily the expansion and evaluation of the road incident characterisation and re-routing capabilities.